Numerical and Field Investigations of Local Bridge Abutment Scour and Unsteady Downstream River Flow From a Nearby Hydropower Plant - Arvydas Šikšnys; Narimantas Titas Ždankus; Gintautas Sabas; Oksana Barvidienė (The Baltic Journal of Road and Bridge Engineering)
Sudden and often fluctuations of water discharges and levels in the downstream reach of the hydropower plant make water fauna and flora existence conditions unbearable. Besides, a riverbed here is subjected to long lasting and intensive scour and deformations. The aim of our investigations is to develop measures improving the water flow regime in the downstream reach of the hydropower plants. The Nemunas River and Kaunas hydropower plants were selected as basis for our numerical and field investigations. Actual flow regime below the hydropower plant was observed and analysed on the ground of the long lasting dynamic measurement data. Numerical treatment of field measurement data and flow simulation works were arranged and carried out simultaneously. Numerical hydrodynamic model MIKE 21 made it possible to evaluate existing river flow conditions and to apply the model for simulation of many different turbine regimes and to select the optimal one. The content of our research was as follows: 1) analysis of typical turbines regimes while switching them on and off and flow regimes downstream; 2) continuous long lasting measurement of water level in many cross-sections of the river under investigation downstream the hydropower plants; 3) numerical simulation and investigation of untypical turbines regimes while switching them on and off and flow regimes downstream with application software MIKE 21 in the same unsteady flow conditions in which field measurements were made; 4) evaluation of the accuracy of hydrodynamic modeling results and possibilities for their application in predicting the local bridge abutment scour. The obtained data on water level and flow rate dynamics downstream the Kaunas hydropower plants have been analysed. Numerical model was developed to simulate the scour at bridge abutment and was calibrated for the same unsteady flow conditions. The obtained accurate results can be used for local bridge abutment scour evaluation.